Laparoscopic versus open pancreatoduodenectomy for pancreatic or periampullary tumours: a multicentre, open-label, randomised controlled trial. (June 2021) - Wang, Min; Li, Dewei; Chen, Rufu; Huang, Xiaobing; Li, Jing; Liu, Yahui; Liu, Jianhua; Cheng, Wei; Chen, Xuemin; Zhao, Wenxing; Li, Jingdong; Tan, Zhijian; et al.
Summary: Background: The benefit and safety of laparoscopic pancreatoduodenectomy (LPD) for the treatment of pancreatic or periampullary tumours remain controversial. Studies have shown that the learning curve plays an important role in LPD, yet there are no randomised studies on LPD after the surgeons have surmounted the learning curve. The aim of this trial was to compare the outcomes of open pancreatoduodenectomy (OPD) with those of LPD, when performed by experienced surgeons. Methods: In this multicentre, open-label, randomised controlled trial done in 14 Chinese medical centres, we recruited patients aged 18–75 years with a benign, premalignant, or malignant indication for pancreatoduodenectomy. Eligible patients were randomly assigned (1:1) to undergo either LPD or OPD. Randomisation was centralised via a computer-generated system that used a block size of four. The patients and surgeons were unmasked to study group, whereas the data collectors, outcome assessors, and data analysts were masked. LPD and OPD were performed by experienced surgeons who had already done at least 104 LPD operations. The primary outcome was the postoperative length of stay. The criteria for discharge were based on functional recovery, and analyses were done on a modified intention-to-treat basis (ie, including patients who had a pancreatoduodenectomy regardless of whether the operation was the one they were assigned to). This trial is registered with Clinicaltrials.gov, number NCT03138213 . Findings: Between May 18, 2018, and Dec 19, 2019, we assessed 762 patients for eligibility, of whom 656 were randomly assigned to either the LPD group (n=328) or the OPD group (n=328). 31 patients in each group were excluded and 80 patients crossed over (33 from LPD to OPD, 47 from OPD to LPD). In the modified intention-to-treat analysis (297 patients in the LPD group and 297 patients in the OPD group), the postoperative length of stay was significantly shorter for patients in the LPD group than for patients in the OPD group (median 15·0 days [95% CI 14·0–16·0] vs 16·0 days [15·0–17·0]; p=0·02). 90-day mortality was similar in both groups (five [2%] of 297 patients in the LPD group vs six [2%] of 297 in the OPD group, risk ratio [RR] 0·83 [95% CI 0·26–2·70]; p=0·76). The incidence rate of serious postoperative morbidities (Clavien-Dindo grade of at least 3) was not significantly different in the two groups (85 [29%] of 297 patients in the LPD group vs 69 [23%] of 297 patients in OPD group, RR 1·23 [95% CI 0·94–1·62]; p=0·13). The comprehensive complication index score was not significantly different between the two groups (median score 8·7 [IQR 0·0–26·2] vs 0·0 [0·0–20·9]; p=0·06). Interpretation: In highly experienced hands, LPD is a safe and feasible procedure. It was associated with a shorter length of stay and similar short-term morbidity and mortality rates to OPD. Nonetheless, the clinical benefit of LPD compared with OPD was marginal despite extensive procedural expertise. Future research should focus on identifying the populations that will benefit from LPD. Funding: National Natural Science Foundation of China and Tongji Hospital, Huazhong University of Science and Technology, China.